Paenibacillus glucanolyticus, a promising potassium solubilizing bacterium isolated from black pepper (Piper nigrum L.) rhizosphere - V Srinivasan, K P Sangeeth, R Suseela Bhai, (Journal of Spices and Aromatic Crops, 2012)
A bacterium possessing high ability to solubilize potash was isolated from the rhizosphere of black pepper. On the basis of biochemical and 16S rDNA sequence analysis, the bacterium was identified as Paenibacillus glucanolyticus strain IISRBK2. The optimal medium composition and cultural conditions for the isolation of P. glucanolyticus were sucrose 5.0 g, Na2HPO4 2.0 g, MgSO4.7H2O 2.0 g, FeCl3 0.005 g, CaCO3 0.1 g and wood ash 1.0 g at pH 7.5 at 30oC. The strain was also evaluated for plant growth and potassium (K) uptake of black pepper in soil artificially treated with 0.5,1 and 1.5g K kg-1 soil in the form of wood ash. In this study, wood ash was used as a source of K which contained 53.1 g Kg-1 K of which 4.5% was in insoluble form. Inoculation with strain P. glucanolyticus was found to increase tissue dry mass (ranging from 37.0% to 68.3%) of black pepper in 1g K kg-1wood ash amended soil. In the soil treated with 0.5 -1.5 g K kg-1, K uptake in live bacterium inoculated black pepper plants increased by 125.0-184.0% compared to uninoculated control.